KEBERADAAN BECAK DALAM PERSFEKTIF KEPARIWISATAAN DI KOTA PONTIANAK - NIM. A1011181115, MUHAMMAD RIQBI (Fakultas Hukum Universitas Tanjungpura, 2022)
Abstract Development in all fields is a government effort in order to improve the welfare of its people. The priority sector in this development is the economic sector. One of the elements is the transportation sector. Indonesia has a lot of diverse local wisdom. Starting from culture, customs, traditions, even in the field of transportation. The transportation in question is a traditional means of transportation, this means of transportation is owned by every region in Indonesia. The means of transportation, namely rickshaw transportation, becak is a three-wheeled transportation tool that has existed since time immemorial and became the prima donna of its time. This vehicle is a modification of a two-wheeled bicycle using a pair of pedals that are pedaled with the feet as a propulsion, which functions to transport people and/or goods in small quantities, then modified into a three-wheeled vehicle equipped with a passenger cabin. The formulation of the problem in this study is